The poetics of Claremont disrupted - Harris, Jennifer (Curtin University, 2012)
Redevelopment of the historic shopping district of Claremont started with extensive demolition. The new development, called Claremont Quarter, is characterised by architecture of non-place and the erasure of much of the old poetics. Visitors are highly directed in how they move around in a heavily planned setting. This is in stark contrast to the remaining old Claremont which is characterised by a rough accretion of walls and buildings constructed over many periods; it offers to visitors many possible ways to use the area. In the redevelopment, the poetics of the district have been entirely disregarded. This paper reflects on the poetics of Claremont arguing that the subtle, dialogic poetics of place is an area of heritage practice which, if it is considered at all, is bracketed under sense of place analysis. Poetics, however, is quite different from sense of place, referring more emphatically to everyday experience; it is open-ended, dialogic, gesturing to the future and bringing place and people together. An understanding of poetics leads necessarily to a richer perception of people's interaction with place that is possible in sense of place analysis. This paper argues that it is time for heritage practice to include poetics as a key aspect of place understanding.